Pengaruh Return on Equity, Current Ratio dan Firm Size Terhadap Financial Distress Bank Syariah Non BUMN yang terdaftar di BEI periode 2015-2021 - Minchatul Maula, Mila; Firdausi, M Izzat; Badarudin, Badarudin (Journal Of Islamic Economics And Finance, 2023)
The bank is a company engaged in the financial sector. Banks function as a forum for public finances that can save and maintain their finances, in a bank must have a vision and mission which includes getting a lot of profit so that the company continues to run and does not experience financial distress. Financial Distress is a condition experienced by an issuer prior to bankruptcy which is marked by a decline in the financial performance of that issuer. This research was conducted to discuss the factors that influence the occurrence of financial distress at Bank Panin Dubai Syariah, Bank Aladin Syariah, Bank BTPN Syariah and Bank Muamalat Indonesia for the 2015-2021 period. This research is a quantitative study using panel data regression and hypothesis testing with the EViews 10 application. The results showed that there was no effect on profitability and liquidity on financial distress, but there was influence of company size on predictions of financial distress for the 2015-2021 period